ETV4 is a useful marker for the diagnosis of CIC-rearranged undifferentiated round-cell sarcomas: a study of 127 cases including mimicking lesions - Le Guellec, Sophie; Velasco, Valérie; Pérot, Gaëlle; Watson, Sarah; Tirode, Franck; Coindre, Jean-Michel (Modern pathology, 2016)
Subsets of primitive round-cell sarcomas remain difficult to diagnose and classify. Among these is a rare round-cell sarcoma that harbors a CIC gene rearrangement known as CIC- rearranged undifferentiated round-cell sarcoma, which is most commonly fused to the DUX4 gene. Owing to its aggressive clinical behavior and potential therapeutic implications, accurate identification of this novel soft tissue sarcoma is necessary. Definitive diagnosis requires molecular confirmation, but only a few centers are as yet able to perform this test. Several studies have shown that PEA3 subfamily genes, notably ETV4 (belonging to the family of ETS transcription factors), are upregulated in CIC- rearranged undifferentiated round-cell sarcomas. We performed a detailed immunohistochemical analysis to investigate ETV4 expression in CIC- rearranged undifferentiated round-cell sarcomas and their potential mimics (especially Ewing sarcomas). The study cohort included 17 cases of CIC- rearranged undifferentiated round-cell sarcomas, and 110 tumors that morphologically mimic CIC- rearranged undifferentiated round-cell sarcomas: 43 Ewing sarcomas, 25 alveolar rhabdomyosarcomas, 20 poorly differentiated round-cell synovial sarcomas, 10 desmoplastic round-cell tumors, 5 BCOR-CCNB3 sarcomas, 5 lymphoblastic lymphomas, and 2 rhabdoid tumors. All CIC- rearranged undifferentiated round-cell sarcomas (on core needle biopsies and open biopsies) were ETV4-positive with a strong diffuse nuclear pattern. Among the other 110 tumors, only six cases (four Ewing sarcomas, one alveolar rhabdomyosarcoma, and one desmoplastic round-cell tumor) showed focal (<5% of tumor cells) and very weak nuclear expression of ETV4; all other tumors were completely negative for ETV4. We conclude that systematic immunohistochemical analysis of ETV4 makes it possible to diagnose undifferentiated round-cell sarcomas (with no molecular markers for sarcoma-associated translocation) such as CIC- rearranged undifferentiated round-cell sarcoma.